2008
DOI: 10.1148/radiol.2463062148
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Pulmonary Nodules: Meta-analytic Comparison of Cross-sectional Imaging Modalities for Diagnosis of Malignancy

Abstract: Dynamic CT and MR, FDG PET, and (99m)Tc-depreotide SPECT are noninvasive and accurate in distinguishing malignant from benign SPNs; differences among these tests are nonsignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
7
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(133 citation statements)
references
References 54 publications
5
115
7
6
Order By: Relevance
“…The 2008 meta-analysis 48 yielded an estimate for the sensitivity of PET scan that was somewhat higher (95%) than the estimate of 87% that we reported in the second edition of these guidelines. 6,39 Among more recent studies identifi ed by our updated literature review, estimates of sensitivity ranged from 72% to 94% ( Table S7 ).…”
Section: Pet Scanning With Fluorodeoxyglucosecontrasting
confidence: 60%
See 1 more Smart Citation
“…The 2008 meta-analysis 48 yielded an estimate for the sensitivity of PET scan that was somewhat higher (95%) than the estimate of 87% that we reported in the second edition of these guidelines. 6,39 Among more recent studies identifi ed by our updated literature review, estimates of sensitivity ranged from 72% to 94% ( Table S7 ).…”
Section: Pet Scanning With Fluorodeoxyglucosecontrasting
confidence: 60%
“…48 Pooled estimates of sensitivity ranged from 93% for dynamic CT scan to 94% for dynamic MRI to 95% for both PET and SPECT scans, whereas pooled specifi city ranged from 76% for dynamic CT scan to 79% for dynamic MRI to 82% for both PET and SPECT scans. Comparison of summary receiver operating characteristic curves showed that there were no signifi cant differences in accuracy among all four modalities.…”
Section: E101smentioning
confidence: 94%
“…43 However, the majority of nodules are benign, even in smokers, raising concerns about over-investigation of potential malignancy. 44 Finally, although some screening studies have suggested improvements in lung cancer mortality in the screened population, other investigators have suggested that this may simply be due to detection of cancer earlier within its natural history or so-called 'lead-time' bias. 45 …”
Section: Chest X-ray and Computed Tomography Screeningmentioning
confidence: 99%
“…(9) One recent meta-analysis reported that dynamic CT and MRI, both of which are noninvasive methods, are equally accurate in distinguishing between malignant and benign solitary pulmonary nodules, the differences between the two tests being insignificant. (10) The authors of that meta-analysis found that, for the 10 dynamic CT studies, MRI had a pooled sensitivity of 93% (95% CI: 0.88-0.97) and a pooled specificity of 76% (95% CI: 0.68-0.97). (10) Koyama et al (11) reported that non-contrastenhanced MRI of the lung is as efficient as is thin-section multidetector CT in detecting malignant nodules.…”
Section: Introductionmentioning
confidence: 99%
“…(10) The authors of that meta-analysis found that, for the 10 dynamic CT studies, MRI had a pooled sensitivity of 93% (95% CI: 0.88-0.97) and a pooled specificity of 76% (95% CI: 0.68-0.97). (10) Koyama et al (11) reported that non-contrastenhanced MRI of the lung is as efficient as is thin-section multidetector CT in detecting malignant nodules. The authors also found that the overall nodule detection rate in each MRI sequence (82.5%) was significantly lower than was that of multidetector CT (97.0%), although there was no significant difference between the two techniques in terms of the detection rate for malignant nodules.…”
Section: Introductionmentioning
confidence: 99%